Modeling drift and fate of microplastics in the Baltic Sea - Murawski, Jens; She, Jun; Frishfelds, Vilnis (Frontiers in Marine Science, 2022)
Marine plastic litter has been recognized as a growing problem and a threat to the marine environment and ecosystems, although its impacts on the marine life are still largely unknown. Marine protection and conservation actions require a detailed knowledge of the marine pathways, sources, and sinks of land-emitted plastic pollution. Model-based assessments provide a systematic way to map the occurrence of microplastics in the marine environment and to link the coastal sources to the accumulation zones in the sea. New modeling capacities have been developed, which include relevant key processes, i.e., current- and wave-induced horizontal and vertical transport, biofilm growth on the particle surface, sinking, and sedimentation. The core engine is the HIROMB-BOOS ocean circulation model, which has been set up for the Baltic Sea in a high, eddy-permitting resolution of approximately 900 m. We introduce the three-dimensional modeling tool for microplastics and demonstrate its ability to reproduce the drift pattern of microplastics in the Baltic Sea. The results of a multiyear run 2014–2019 provide the basis for an extensive validation study, which allows the evaluation of the model quality. The assessments focus on three types of microplastics, from car tires and household products, with different densities and particle sizes, which cover a broad range of land-emitted microplastic pollution. We show that the model is applicable to the task of identifying high concentration zones in the Baltic Sea and that it can be a useful tool to support the study of the environmental impacts of microplastics in the Baltic Sea. Our results suggest that microplastic concentrations in coastal regions close to major sources reach values above 0.0001 g/m3 near the surface, dependent on the buoyancy of the plastic material and the amount of discharge. The comparison with observations shows that the model is able to reproduce the average concentrations of measured microplastics in the size class of 300 μm with statistical significance, but it underestimates the very high concentrations associated either with flooding or high river-runoff events or generated by sub-mesoscale transport. The model is able to reproduce the seasonal dynamic in Latvian and Estonian waters, except for October, when the increase of modelled microplastics in the ocean is too slow. But the general spatial patterns are sufficiently well reproduced, which makes the developed model a tool sufficient for the assessment of microplastic transport and accumulation pattern.